School to Work Transition for Young People with Disability in Vietnam - Nguyen, Huong Thi Thu (Curtin University, 2020)
This research examined factors impacting on the success of school to work transition for young people with disability in Vietnam. Using a mixed methods case study, information was collected from young people with disability, their families, policy makers and service providers. The research highlights the value of a transition program and suggests support services address specific impairments, and agencies implement their legal roles to ensure the rights of young people with disability towards inclusive employment.